Roadmap for Accelerated Domestication of an Emerging Perennial Grain Crop. (June 2020) - DeHaan, Lee; Larson, Steve; López-Marqués, Rosa L.; Wenkel, Stephan; Gao, Caixia; Palmgren, Michael
Abstract : Shifting the life cycle of grain crops from annual to perennial would usher in a new era of agriculture that is more environmentally friendly, resilient to climate change, and capable of soil carbon sequestration. Despite decades of work, transforming the annual grain crop wheat ( Triticum aestivum ) into a perennial has yet to be realized. Direct domestication of wild perennial grass relatives of wheat, such as Thinopyrum intermedium, is an alternative approach. Here we highlight protein coding sequences in the recently released T. intermedium genome sequence that may be orthologous to domestication genes identified in annual grain crops. Their presence suggests a roadmap for the accelerated domestication of this plant using new breeding technologies. Highlights: Current grain crops are annuals that must be sown every year, giving their root systems little time to develop during the growing season. A perennial grain crop with a long-lived extensive root system would improve soil quality, store carbon belowground, and utilize water and minerals more efficiently. Domestication genes of the annual grass wheat are highly conserved in the perennial intermediate wheatgrass ( Thinopyrum intermedium ), providing an opportunity for accelerated domestication of a perennial grain using a mutagenesis approach.